The new social contract and the conservative remoulding of the West - Lewkowicz, Nicolas (Rivista di studi politici internazionali, 2013)
This paper charts the historical evolution of the social contract, paying particular attention to the implications of the link between economic ‘enclosures’ and the concept of political representation. The Author outlines the ways in which the social contract underwent a meliorist reordering in the aftermath of World War Two and how, since the 1970s, tables are being turned in favour of the return to the minimal State. The paper posits the idea that the severance of the link between political action and economic improvement is consolidating conservative democracy as the political consciousness of the ‘Market-state’. The Author describes how this philosophy is reshaping the societal make-up of Western societies with the use of motivational rhetoric, which is geared towards facilitating the reversal of the meliorist social contract.L’article montre l’évolution historique du contrat social et mets en évidence le lien entre les enceintes économiques et le concept de représentation politique. L’Auteur souligne les façons par lesquelles le contrat social subit une réordination méliorative après la deuxième guerre mondiale, et le fait que, à partir des années ’70, il y a en un revirement en faveur de l’État minimal. L’Auteur soutient que, en coupant le lien entre action politique et progrès économique on a consolidé la démocratie conservative, en tant que conscience politique de l’État-marché. L’Auteur décrit comment cette philosophie est en train de réorganiser la constitution societaire des sociétés occidentales par l’emploi d’une rhétorique motivationale, qui vise à faciliter le renversement du contrat social mélioratif.KEY-WORDS: Meliorist social contract; Conservative democracy; Enclosures; ‘Propertynexus’; ‘Market-state’.